2020
DOI: 10.1101/2020.04.20.20065953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The production and clinical implications of SARS-CoV-2 antibodies

Abstract: Funding 1. Chongqing Education Board "new coronavirus infection and prevention" emergency scientific research project (KYYJ202006).2. Chongqing Science and Technology Bureau "new crown pneumonia epidemic emergency science and technology special" the fourth batch of projects. Famous teacher project of Chongqing talent planAll rights reserved. No reuse allowed without permission. AbstractBackground: Severe acute respiratory syndrome coronavirus 2(SARS-CoV-2), a novel betacoronavirus, has caused an outburst of pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 28 publications
2
24
0
2
Order By: Relevance
“…Older adults • Five studies found no association between antibody response and age, for both antibody positivity 147 or IgM/IgG titre. 21,58,148,167 • One study found that 'older' patients were more likely to seroconvert, 153 and concentration of IgG was related to age.…”
Section: Agementioning
confidence: 96%
See 3 more Smart Citations
“…Older adults • Five studies found no association between antibody response and age, for both antibody positivity 147 or IgM/IgG titre. 21,58,148,167 • One study found that 'older' patients were more likely to seroconvert, 153 and concentration of IgG was related to age.…”
Section: Agementioning
confidence: 96%
“…40,43,62,63 Virus-specific IgM became undetectable in almost all cases by around six weeks after disease onset in two small but high quality cohort studies. 53,64 Fewer studies describe IgA dynamics compared to IgM or IgG. IgA levels are reported to peak between 16 -22 days post symptom onset, although there is no consensus on trends over time.…”
Section: Antibody Dynamics Over Timementioning
confidence: 99%
See 2 more Smart Citations
“…Ancak, antikor konsantrasyonunun enfeksiyonun seyrini ve sonucunu etkilemediği görülmüştür. Ayrıca iyileşme sırasında saptanabilir düzeyde SARS-CoV-2 RNA pozitifliği olanlarda da IgG konsantrasyonlarının düşük olduğu gösterilmiştir (27) .…”
Section: ) Serolojik Testlerunclassified